Digital Activism Rancangan Undang – Undang Tindak Pidana Kekerasan Seksual : (Analisis Jaringan Komunikasi terkait isu RUU TPKS di Twitter) - Ramadhani, Alif; Arianto, Irwan Dwi (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2022)
Cases of sexual violence that appeared continuously in December 2021, increased the discussion on Twitter regarding the issue of the ratification of the Draft Law on the Crime of Sexual Violence.The high level of discussion gave rise to digital activism in the form of encouragement and pressure to ratify the RUU TPKS. But on the other hand, the urgency of sexual violence that emerged during the discussion of the RUU TPKS did not make all parties agree with the digital activism movement to ratify the RUU TPKS. These differences generate debates to form a communication network. The network formed consists of clusters consisting of actors involved in it. This study aims to map the communication network that is formed on the issue of the RUU TPKS, using the keyword